Mental Models in Chemistry Concept: A Systematic Review - Andi Tenri Uleng; Muthmainnah Damsi; Yanti Kumala Sembiring (Jurnal Penelitian Pendidikan IPA, 2024)
Mental models in chemistry concepts are defined as student’s comprehension of three levels of chemical representations, including macroscopic, submicroscopic, and symbolic levels. This study aims to identify, review, and evaluate research concerning mental models in chemistry concepts through specific research questions. The research method used is a systematic literature review (SLR) by analyzing relevant articles from Google Scholar, Eric, Scopus, and Crosscref, focusing on publications from the the past decade (2013–2023). A total of 52 articles were obtained from the analysis based on the inclusion and exclusion criteria. The findings indicate that most studies aim to understand students' mental model profiles related to chemistry concepts. High school students are predominantly involved as research samples. The most used data collection tool is diagnostic tests. Mental models are primarily studied in physical chemistry, particularly in chemical equilibrium, adopting various theories, especially the Sendur, Toprak, and Pekmez (2010) model. Factors influencing the formation of students' mental models include internal factors such as prior knowledge, experiences, attitudes, and motivations, and external factors such as the environment, incomplete textbooks, and inappropriate teaching strategies.